STUDENTS' QUESTIONING SKILLS IN ENVIRONMENTAL POLLUTION COURSE USING CASE STUDY METHODS - Zenia Lutfi Kurniawati; Ruqoyyah Nasution; Jailani Jailani; Syahril Bardin (ScienceEdu, 2021)
Questioning skills are very important for prospective teacher students to master in order to help students learn actively in class later. Students' questioning skills are empowered through case study learning of environmental pollution subjects. Because it discusses pollution in the environment, a solution needs to be found. The purpose of this study was to determine the questioning skills of prospective teacher students in environmental pollution course using case study method. This qualitative descriptive research was conducted in the odd semester of the 2020/2021 academic year. The measurement instrument was in the form of scoring the students' questioning skill level based on the cognitive level of the revised bloom taxonomy. The research data were analyzed by using the percentage technique. The results showed that the questions asked by students at the low order thinking skills level were 83.33% and the high order thinking skills level was 26.66%. Furthermore, it is necessary to habituate students with asking questions with more intensive assistance and lecturers can provide more examples of questions at the high order thinking skills level.